IMPACT OF SOCIAL MEDIA USE: ANALYSIS OF CHARACTER CHANGE IN ISLAM - Imam Tabroni; Elsa Kurniawati; Nurul Fadilah; Robiah Al Adawiyah (Jurnal Riset Rumpun Agama dan Filsafat, 2022)
Social media is an online medium, with its users being able to easily participate, share, and create content including blogs, social networks, wikis, forums and virtual worlds. Blogs, social networks and wikis are the most common forms of social media used by people around the world. The positive impact of social media is that it makes it easier for us to interact with many people, expand relationships, distance and time are no longer a problem, easier to express ourselves, information dissemination can take place quickly, costs are cheaper. While the negative impact of social media is to keep people who are close and vice versa, face-to-face interactions tend to decrease, making people addicted to the internet, causing conflicts, privacy problems, vulnerable to bad influences from others. The existence of social media has influenced social life in society. Changes in social relationships or as changes to the balance (equilibrium) of social relations and all forms of changes in social institutions in a society, which affect the social system, including values, attitudes and behavior patterns among groups in society. Positive social changes such as the ease of obtaining and conveying information, obtaining social and economic benefits. Meanwhile, social changes tend to be negative, such as the emergence of social groups in the name of religion, ethnicity and certain behavioral patterns that sometimes deviate from existing norms.